2021
DOI: 10.1002/ejhf.2200
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial structure and function of the amyloidogenic V122I transthyretin variant in elderly African Americans

Abstract: Aims African‐American carriers of the transthyretin (TTR) valine‐to‐isoleucine substitution (V122I) are at increased risk of heart failure, yet many have relatively subtle abnormalities of left ventricular (LV) function. We sought to explore the influence of this mutation on left atrial (LA) structure and function in this population. Methods and results We assessed 1225 genotyped African‐Americans (age range, 67–89 years) participating in the Atherosclerosis Risk in Communities study who underwent echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Multiple studies have demonstrated that LA dysfunction may precede changes in LA structure. 14 , 15 , 16 , 17 Thus, we speculate that the changes in LA function may be more sensitive than those of LA volume in detecting LA remodeling, which should be investigated in future researche.…”
Section: Discussionmentioning
confidence: 91%
“…Multiple studies have demonstrated that LA dysfunction may precede changes in LA structure. 14 , 15 , 16 , 17 Thus, we speculate that the changes in LA function may be more sensitive than those of LA volume in detecting LA remodeling, which should be investigated in future researche.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, speckle tracking allows the detection of differences not only in overt disease manifestation but also in the subclinical setting. Specifically, if, on one side, left atrial dysfunction proves to be more pronounced in ATTR (compared to AL) patients, despite left atrial volumes being comparable [ 22 ], on the other side, the detection of left atrial abnormalities in carriers with a transthyretin valine-to-isoleucine substitution underlines subtle left ventricular remodeling [ 23 ].…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…Increased incidence of intracardiac thrombi despite the absence of AF/flutter [ 22 , 23 , 24 , 24 , 25 , 26 ]…”
Section: Figurementioning
confidence: 99%
“…On the other hand, a role of amyloid‐mediated damage is suggested by pathophysiological considerations, and the evidence of atrial wall thickening and increased stiffness by cardiovascular magnetic resonance (CMR). We may also consider that LA size is the parameter most directly affected by filling pressures, and that LA stiffness (defined as the ratio between E/e′ and LA strain reservoir) is higher than expected based on LA size alone, 6 , 8 again pointing to a role of atrial wall disease.…”
Section: Visualization Of Atrial Dysfunctionmentioning
confidence: 99%
“… 4 , 5 , 6 The right atrium (RA) may be similarly affected. Atrial amyloidosis develops in early stages of AL‐ and ATTR‐CA, 7 , 8 and is associated with an increased risk of supraventricular arrhythmias and thromboembolic events. Furthermore, atrial amyloidosis can be found even in the absence of systemic disease and LV involvement.…”
Section: Introductionmentioning
confidence: 99%